Effects of Oblique Incidence of SV Waves on Nonlinear Seismic Response of a Lined Arched Tunnel. (20th February 2020) - Lyu, Dunyu; Ma, Sha; Yu, Chu; Liu, Congcong; Wang, Xiaowei; Yang, Buyun; Xiao, Ming
Abstract : The incident direction of earthquake motion is an important factor affecting the seismic response of underground structures. In this study, a three-dimensional (3D) oblique incidence method of SV waves is proposed and the effects of incident angles of SV waves on the seismic response of a lined arched tunnel are evaluated. Based on wave field decomposition principle and equivalent node force method and together with viscous-spring artificial boundary, the oblique incidence method of SV waves is implemented by transforming seismic wave field into the equivalent nodal forces acting on the artificial boundaries. By deriving the distance of the incident waves and the reflected wave on free surface to artificial boundaries, this method can comprehensively consider the phase difference of the seismic wave propagation and the influence of the damping effect of the rock medium on the seismic wave propagation. The method is programed into a dynamic finite element program and its effectiveness is examined by a numerical example. Consequently, the oblique incidence method is applied to evaluate the seismic behaviors of the tunnel. The numerical results reveal that (1) the oblique incidence of the seismic wave results in a larger seismic response; (2) the response amplitudes of the stress and displacement increase with the increase of incident angles and reaching the maximum in the case of 30° incident angle; (3) the damage extent increases with an increase in the incident angles, and the oblique incidence of the seismic wave is believed to increase the spatial difference of damage distribution.